Estrategias y mejoras operativas aplicadas a la gestión de inventarios y operaciones para obtener eficiencia operativa - Villagra Chavez, Néstor Jesus (2021)
The present paper aims to develop operations and inventory management strategies in the warehouse of the client América Móvil S.A to obtain better operational efficiency with a high level of service. This occurs within the facilities of logistic operations Ransa S.A, which is located in the constitutional province of Callao and interacts in the business sector with companies from various sectors, mainly those that participate in development and service to the country. A methodology based on the strategic map was used to achieve the main and specific objectives of the operation. The definition of the main objective is relevant to define the actions that will be measured with indicators for decision-making, prior to the identification of problems and needs of both, the client and the organization. In addition, an analysis of the business environment at the local and regional levels where Ransa operates was carried out. The focus is always to achieve customer satisfaction based on operations and inventory management. To boost the company's service, it is proposed to develop a series of strategies reflecting the desired results in operations and inventory levels. Finally, the order and precision of a storage operation will help us to be efficient, therefore, be more productive, generating lower operating costs and savings for the organization and the client.